An empirical investigation of fault types in space mission system software - Grottke, Michael; Nikora, Allen; Trivedi, Kishor (40th Annual IEEE/IFIP International Conference on Dependable Systems and Networks, 2010)
As space mission software becomes more complex, the ability to effectively deal with faults is increasingly important. The strategies that can be employed for fighting a software bug depend on its fault type. Bohrbugs are easily isolated and removed during software testing. Mandelbugs appear to behave chaotically. While it is more difficult to detect these faults during testing, it may not be necessary to correct them; a simple retry after a failure occurrence may work. Aging-related bugs, a sub-class of Mandelbugs, can cause an increasing failure rate. For these faults, proactive techniques may prevent future failures. In this paper, we analyze the faults discovered in the on-board software for 18 JPL/NASA space missions. We present the proportions of the various fault types and study how they have evolved over time. Moreover, we examine whether or not the fault type and attributes such as the failure effect are independent. © 2010 IEEE.
WiSo-Import:2015-04-17:1354
Keywords: Innovation